Importance of preserving the natural environment in the design schools in Malaysia - Hashim, Haikal Hazman; Denan, Zuraini (Elsevier, 2015)
The atmosphere of a learning environment is crucial in stimulating the design students in producing creative works. Preserving the green, retaining most of part the topography and balancing with the climate is the core of sustainable design, which is the vital life principle for all humankind. The research attempts to investigate the importance of preserving the natural environment of design schools, based on the analysis of observation and questionnaire surveys. For a preliminary study, the research analysed three samples of design schools in Selangor, Malaysia. Findings indicate that students prefer having natural environment in surrounding, and it can stimulate the students’ creativity process.